2003
DOI: 10.2214/ajr.181.3.1810695
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Events During Radiofrequency Treatment of 582 Hepatic Tumors

Abstract: Radiofrequency ablation of liver tumors is a well-tolerated technique, but caution should be exercised when treating patients with a bilioenteric anastomosis, and radiofrequency ablation during vascular occlusion in cirrhotic livers should be avoided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
301
4
6

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 438 publications
(321 citation statements)
references
References 35 publications
10
301
4
6
Order By: Relevance
“…All of the rest are considered minor [3] . Authors have reported rates as low as 2% to 5.7% for major complications [4][5][6] . Mortality related to the procedure is low, reported in the literature to be less than 1% [7][8][9] .…”
Section: Topic Highlightmentioning
confidence: 99%
See 2 more Smart Citations
“…All of the rest are considered minor [3] . Authors have reported rates as low as 2% to 5.7% for major complications [4][5][6] . Mortality related to the procedure is low, reported in the literature to be less than 1% [7][8][9] .…”
Section: Topic Highlightmentioning
confidence: 99%
“…Intra-abdominal bleeding is the most common complication encountered in many studies [5,6,12,13] . In Mulier's review, it occurred in 0.7% of the procedures in 3670 patients [12] .…”
Section: Hemorrhagic Complicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the cutting-edge technologies, is highlighting the use of RF as well known in the therapeutic armamentarium ablation of liver lesions 3,4,11,12,21 . Recent studies have shown 3,13,14,22,25 hepatectomies performed using the monopolar RF, where the blood loss and the occurrence of fistula bile was almost nil.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, the RF ablation of tumors has allowed patients with low functional reserve had controlled their lesions, leading to waiting for transplantation in patients with primary tumors 4,11,12 , or allowing an increase in its survival in cases of metastatic lesions 21 . However, despite the appropriate use of RF ablation, local recurrence at the site of ablation varies around 40% 3 .…”
Section: Discussionmentioning
confidence: 99%